2016
DOI: 10.1534/genetics.115.184234
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Haploid Induction in Maize Identified with a Novel Genome-Wide Association Method

Abstract: In vivo haploid induction (HI) triggered by pollination with special intraspecific genotypes, called inducers, is unique to Zea mays L. within the plant kingdom and has revolutionized maize breeding during the last decade. However, the molecular mechanisms underlying HI in maize are still unclear. To investigate the genetic basis of HI, we developed a new approach for genome-wide association studies (GWAS), termed conditional haplotype extension (CHE) test that allows detection of selective sweeps even under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
4
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 43 publications
2
71
4
5
Order By: Relevance
“…The study clearly revealed that qhir11 is the only sub-region with a strong effect on HIR, whereas qhir12 had a negligible effect on HIR, in contrast to the hypothesis of Hu et al (2016) based on a selective sweep based GWAS approach. Furthermore, our study proved that qhir11 is more strongly associated than qhir12 with segregation distortion and kernel abortion, two traits that are associated with maternal haploid induction.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The study clearly revealed that qhir11 is the only sub-region with a strong effect on HIR, whereas qhir12 had a negligible effect on HIR, in contrast to the hypothesis of Hu et al (2016) based on a selective sweep based GWAS approach. Furthermore, our study proved that qhir11 is more strongly associated than qhir12 with segregation distortion and kernel abortion, two traits that are associated with maternal haploid induction.…”
Section: Discussioncontrasting
confidence: 66%
“…The qhir11 sub-region, also found significant in the study by Hu et al (2016), revealed two haplotypes, where the minor haplotype was shared by two non-inducer lines, which did not have HI ability. Additionally, Hu et al (2016) identified qhir12 as the most probable genomic segment carrying gene(s) responsible for HI, as this region had a single haplotype that was unchanged in all the inducers.…”
Section: Discussionmentioning
confidence: 50%
“…In particular, lines EM1201 and Nys302, which have the same haplotype at the gim1/qhir1 locus as the inducer line PK6 except for the 4‐bp insertion, do not induce gynogenesis. This diagnostic indel is also absent in the lines Mo1W and TX303 used as non‐inducer controls in a GWAS study of gim1/qhir1 (Hu et al , ). This later result highlights the preponderant role of the sub‐region qhir11 (containing NLD ) compared to the sub‐region qhir12 (downstream of NLD ) in haploid induction phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…During the past two decades, the traditional method of breeding homozygous inbreds by several generations of recurrent selfing has been complemented by the doubled haploid (DH) technology based on maternal in vivo haploid induction (Molenaar & Melchinger, ). This applies to both temperate and tropical maize, because meanwhile a wide variety of inducers adapted to different climatic zones has become available (Chaikam et al, ; Dong et al, ; Hu et al, ). In addition to the important advantages in breeding summarized by Molenaar and Melchinger (), DH line production is very appealing to breeders because it can be performed with relatively simple equipment and involves only four basic steps: (a) induction of maternal haploids by pollination with haploid inducers (genotypes triggering formation of seeds with haploid embryo), (b) discrimination of haploid seeds from normal crossing seeds, where the embryo contains paternal DNA, (c) chromosome doubling by treatment with chemical agents or occurring spontaneously and (d) selfing of fertile D 0 plants to produce D 1 ears with seed set.…”
Section: Introductionmentioning
confidence: 99%